1978
DOI: 10.1192/bjp.132.6.548
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and Plasma Amine Oxidase Activity in Alcoholic Individuals

Abstract: Platelet and plasma amine oxidase activity was determined in a group of 99 healthy male (active duty military) alcoholics referred for hospital treatment who had been abstinent from alcohol for 2-10 days, and compared with that of a control military group. Platelet MAO activity was slightly but significantly lower in the alcoholic group. Both groups were significantly lower in MAO activity compared to a group of 42 non-military controls. In the alcoholic group there was no correlation between platelet MAO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Platelet MAO (MAO-B) activity has been the subject of great interest in psychiatry since Murphy and Wyatt (1972) reported MAO activity to be lower in chronic schizophrenics than in controls. Low platelet MAO activity has also been associated with alcoholism (Major and Murphy, 1978;Sullivan et al, 1979). Moreover, Major and Murphy (1978) found that first-degree relatives of alcoholics exhibiting low MAO-B activity as well as relatives of controls with low MAO-B activity had a higher incidence of alcoholism than the relatives of high-MAO alcoholics and normal controls.…”
Section: Introductionmentioning
confidence: 96%
“…Platelet MAO (MAO-B) activity has been the subject of great interest in psychiatry since Murphy and Wyatt (1972) reported MAO activity to be lower in chronic schizophrenics than in controls. Low platelet MAO activity has also been associated with alcoholism (Major and Murphy, 1978;Sullivan et al, 1979). Moreover, Major and Murphy (1978) found that first-degree relatives of alcoholics exhibiting low MAO-B activity as well as relatives of controls with low MAO-B activity had a higher incidence of alcoholism than the relatives of high-MAO alcoholics and normal controls.…”
Section: Introductionmentioning
confidence: 96%
“…In relation to reckless behavior, a study of 18-year-old Swedish draftees found that low-MAO males were higher in SSS scores than high-MAO males, and the low-MAO males were also more likely to report reckless behavior such as drug use and criminality (von Knorring, Oreland, & Winbald, 1983). Low MAO levels are also characteristic of alcoholics (Major & Murphy, 1978) and chronic marijuana users (Stillman et al, 1978). Since MAO is negatively correlated with sensation seeking and sensation seeking is negatively correlated with age, one might reasonably expect to find that MAO levels increase with age; one study (Robinson, Davis, Nies, Ravaris, & Sylvester, 1971) bears this out, although another (Murphy, Wright, Buchsbaum, Nichols, Costa, & Wyatt, 1976) reports no age differences in MAO levels.…”
Section: Sensation Seekingmentioning
confidence: 99%
“…While these studies do not rule out a pharma cological effect of these drugs on platelet MAO, the finding of low MAO in relatives of alcoholics [Sullivan et al. 1979;Major and Murphy, 1978] and alcoholism in relatives of probands with low MAO [Puchall et al, 1980] tends to suggest that drug use may be part of the low-MAO syndrome rather than merely an artifact.…”
Section: Discussionmentioning
confidence: 99%